1998
DOI: 10.1002/(sici)1097-0142(19980425)84:2<109::aid-cncr7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

nm23 protein expression in fine-needle aspirates from breast carcinoma

Abstract: nm23 protein showed a significant inverse correlation with lymph node status, cytologic grading, and ploidy. The nm23 protein antibody may have potential as a preoperative marker in identifying subgroups of patients who either may have a worse prognosis than expected (e.g., those with G1 carcinomas with reduced nm23 expression) or who may be able to avoid axillary lymph node dissection (e.g., those with G1 carcinoma with full nm23 protein expression). Cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Nm23 genes have been proposed as metastasis suppressor genes based on clinical studies, which exhibited a correlation between development of metastatic disease and reduced NDPK protein and/or mRNA levels in many but not all cancers (for review, see Backer and Hamby, 1998). However, the role of these genes as metastasis suppressors is controversal since in more recent clinicial studies an association between metastatic potential and nm23 protein levels has not been found in patients with melanoma (Easty et al , 1996; van den Oord et al , 1997) and conflicting results have been obtained in studies of patients with breast carcinoma (Heimann et al ., 1998; Sauer et al , 1997; Russell et al ., 1997; Sawan et al ., 1997). Several factors complicate the interpretation of correlation studies.…”
mentioning
confidence: 99%
“…Nm23 genes have been proposed as metastasis suppressor genes based on clinical studies, which exhibited a correlation between development of metastatic disease and reduced NDPK protein and/or mRNA levels in many but not all cancers (for review, see Backer and Hamby, 1998). However, the role of these genes as metastasis suppressors is controversal since in more recent clinicial studies an association between metastatic potential and nm23 protein levels has not been found in patients with melanoma (Easty et al , 1996; van den Oord et al , 1997) and conflicting results have been obtained in studies of patients with breast carcinoma (Heimann et al ., 1998; Sauer et al , 1997; Russell et al ., 1997; Sawan et al ., 1997). Several factors complicate the interpretation of correlation studies.…”
mentioning
confidence: 99%
“…NM23 was originally described as non-metastatic gene 23, which was found in mouse carcinoma cells and was thought to be inversely related to metastasis (Postel, 2003; Palmieri et al , 2006) although this has been controversial. There is evidence to support an intracellular role for NM23/NDPK in tumour metastasis (Hamby et al , 2000; Roymans et al , 2002), and high tissue levels of NDPK-A protein have been found in patients with breast carcinoma (Heimann et al , 1998; Sauer et al , 1998). Nucleoside diphosphate kinases are secreted by various solid and haematological malignancies (Anzinger et al , 2001; Niitsu et al , 2001; Okabe-Kado et al , 2005a) and promote growth of acute myelogenous leukaemia cells (Okabe-Kado et al , 2009b) and endothelial cells in vitro (Rumjahn et al , 2007).…”
mentioning
confidence: 99%
“…The hypothesis that there is a role for a shed or secreted form of NM23/NDPK subserving breast cancer development has suffered from the NM23 dogma of Steeg [66] and others if the staunch criticism we have received is any measure. Nonetheless, it is clear from in vitro [61,67,68] and recent in vivo work from our lab [69] together with published work from others [34,45-47] that secreted NM23 contributes to our understanding of metastatic potential.…”
Section: Discussionmentioning
confidence: 99%